MENGUNGKAP MISKONSEPSI FISIKA DENGAN METODE THE THREE-TIER TEST - Dwi Ratnaningdyah (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2018)
This paper is the result of a literature review of The Three Tier-Test method in disclosing the physics misconception of the students. Misconception is a condition in which a person has a false or incorrect concept of physics. Misconception in Physics lessons is experienced by many students in school and collages. This misconception is got by students from everyday experiences in the home and school environment because of poor teaching methods. There are various ways to know if a person has misconception or not. Among these are using the CRI (Certainty Response Index) method and the TTT (Three Tier-Test) method. These methods use multilevel questions in which learners should answer the concept correctly and then they have to answer the next level of questions. The TTT method question consists of three levels of questions: core questions (questions that measure conceptual understanding), the reason why choosing the previous answer, and the last question is the level of confidence of learners in answering the test. With this method, the misconceptions of learners will be seen and can be acted upon according to the results obtained.Keyword— misconception, Three-Tier Test (TTT), physics learning